Social Media's Influence on Destination Choice : Trends and Insights - Chaminda Bandara; Ishani Kumaratunga; Lasith Jayawardene (International Conference On Digital Advanced Tourism Management And Technology, 2023)
Social media platforms have become pivotal in influencing travel decisions and destination choices. This study investigates trends in user-generated content, influencer marketing, and platform analytics. Findings reveal how social media campaigns shape perceptions of destinations, contributing to increased bookings and traveler loyalty.